Multispecies analysis of social effects on same-sex sexual behavior challenges mistaken identity hypotheses in insects - Thomas M. J. Green; Jack G. Rayner; Daniel A. Villar; Nathan W. Bailey (Proceedings of the National Academy of Sciences, 2026)
Same-sex sexual behavior (SSB) in insects has historically been considered a byproduct of sex recognition failure, or “mistaken identity,” and consideration of other hypotheses lags behind that of vertebrates where it is often thought to adaptively mitigate aggressive interactions. Comparative analyses to help disentangle the functions of insect SSB are lacking. To address this, we quantified male–male interactions in controlled trials across eight North American field cricket species ( Gryllus spp.). While limited taxonomic sampling precluded a formal phylogenetic comparative analysis, we were able to assess variation across species with structural equation models. Using this technique, we distinguished focal from partner influences and evaluated support for mistaken identity vs. other models of SSB. SSB expression varied extensively across species. It was always associated with reduced aggression, but the strength of this association and the balance of focal vs. partner effects varied. Temporal analysis of behavioral interactions showed that males exhibited SSB while able to discern the sex of their partner. These findings, along with observations of a previously undescribed sexual behavior not seen in different-sex interactions, imply a history of adaptive evolution inconsistent with mistaken identity SSB.